PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Mahasiswa Unisma Fakultas Ekonomi dan Bisnis Jurusan Manajemen JL. MT Haryono 193 Malang) - Muhammad Misnarum; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT                                                  Technological developments in Indonesia are growing through innovations made by the public in using the internet facility. Internet has an important role to support the development of e-commerce to make online transaction. Many transportation online, making people more often make the purchase decision for a product or services. In the purchase decision there are several factors that support is trust, ease of use, and quality of information with these three factors a person is able to take the decision to purchase the product or not.This research is explanative using a qualitative approach. The population in this study are UNISMA students majoring in management who have used the services of go-jek, so that the purposive sampling and sample of 93 respondents using a scale of liker 5 points. Methods of data collection are done by giving questionnaires. Data processing conducted with technique of multiple regression analysis to test the hypothesis simultaneously and partially Results of the analysis showed that consumers had a enough good response to the trust, ease of use, quality of information and purchasing decisions. By simulate trust, ease of use and quality of information have significant effect of  9,846. By partial showed that trust and ease of use have not significant effect on the purchase decision and than quality of information have significant effect on the purchase decision. Keyword : Trust, Ease of use, and Quality of Information